The Relationship of Religion and State Law in Indonesia Paradigm Theory Perspective of the Relationship Between Religion and the State - Ahmad Musadad (Universitas Nurul Jadid, 2023)
The discourse on the relationship between religion and the state in the context of the implementation of Islamic law in Indonesia is an issue that will never go stale. This article aims to examine the relationship between Islamic law and state law from a paradigm theoretical perspective on the relationship between religion and the state, a study of the thoughts of Indonesian thinker Prof. Arskal Salim. The type of method used is qualitative, data comes from library materials, the main data is the book